Factors that influence eldery to age in place in Sabah - Lim, Elise Wei Xin (2024)
This research was carried out to study the factors that influence elderly to age in place in Sabah. Four factors had been tested which are social support, environmental factors, housing features and physical and mental health. This study applied a quantitative research method. The target population of this research is those who aged above 60, residing in Sabah state. Primary data of this research was obtained through the distribution of 100 copies of questionnaires and was analyzed using the SPSS software.